Pairing Fieldworkers with Patrol Officers: A Study of Supervising Officers' Selections. (16th April 2017) - Allen, Andrea; Jacques, Scott
Abstract: Qualitative, field-based studies of police tend not to rely on random sampling, but, instead, navigate a well-trodden path to cases. The first step is gaining a supervising officer's (SO) consent to study their department, and the last step is convincing patrol officers (POs) to reveal what they normally do and think. Also, there is an indispensable intermediary step in which fieldworkers are paired with particular POs, a choice sometimes left up to SOs. Despite its importance, the basis on which such couplings are made is not well documented, much less understood. Thus, this article analyzes qualitative data obtained from nine SOs about why they assigned particular POs to accompany the first-author on ride-alongs. The SOs largely explained their assignments as meant to help the research by placing the fieldworker with POs who would yield more data in terms of quantity, variety, and 'better' answers. The article concludes by discussing the findings' broader implications.